A historical overview of the Wärğəḥ Muslim community in the Christian highland of Šäwa - Deresse Ayenachew (Afriques)
The Wärğəḥ Muslim community constitutes more than 22,000 people in Ethiopia. They live in diverse parts of the country, but the largest number of Wärğəḥ are found in north Šäwa and near Dəre Dawa. In north Šäwa, the community of Wärğəḥ has established scattered pockets of villages between Däbrä Berhan and Säbäta towns. Linguistically, they speak Oromo and also Amharic. Fragmentary medieval Ethiopian historical sources describe the Wärğəḥ as inhabitants of the lowlands of south-east Šäwa. They were herdsmen, particularly camel keepers. Post-16th century sources record that the Wärğəḥ transformed their way of life to become traders following the great medieval caravan trade routes. Due to their resistance against expansions, they were described as warriors and a ferocious people. For the purpose of this paper, we have gathered oral accounts from 13 local villages of north Šäwa to identify how these people reconstruct their history and to understand how all these villages networked with each other to endure the waves of dynamic religious and population movements of these periods. Funerary stelae were also surveyed to determine whether their styles could be related to the megalithic cultures of south-west Ethiopia.